2019
DOI: 10.3390/dj7030074
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion to Zirconia: A Systematic Review of Current Conditioning Methods and Bonding Materials

Abstract: Background. Reliable bonding between resin composite cements and high strength ceramics is difficult to achieve because of their chemical inertness and lack of silica content that makes etching impossible. The purpose of this review is to classify and analyze the existing methods and materials suggested to improve the adhesion of zirconia to dental substrate by using composite resins, in order to explore current trends in surface conditioning methods with predictable results. Methods. The current literature, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
96
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 101 publications
(126 reference statements)
3
96
0
3
Order By: Relevance
“…Although this primers have been reported to increase adhesion by chemical interactions between the Y-TZP surface and resin cement [ 18 , 19 ], some studies have shown that the bond strength of sintered Y-TZP surface-treated with zirconia primers is significantly reduced after aging process [ 20 , 21 ]. Therefore, no consensus yet exists for what is the effective bonding method to Y-TZP prosthesis [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although this primers have been reported to increase adhesion by chemical interactions between the Y-TZP surface and resin cement [ 18 , 19 ], some studies have shown that the bond strength of sintered Y-TZP surface-treated with zirconia primers is significantly reduced after aging process [ 20 , 21 ]. Therefore, no consensus yet exists for what is the effective bonding method to Y-TZP prosthesis [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the use of sandblasting and functional monomer-containing resin cement shows reliable clinical bonding to zirconia ceramic [9,12,13,14,17]. However, until now, there has been no definitive protocol for the most effective bonding to zirconia prosthesis [10,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The conducted analyses drew the conclusion that a combination of mechanical and chemical treatments is essential for good adhesion. However, they revealed that currently there is a lack of evidence to support a universal adhesion protocol [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%